S–scheme TiO2/ZnS heterojunction as dual-reaction sites: A high–efficiency and spontaneous photocatalyst for hydrogen production under light irradiation. (April 2023) - Li, Dongxiang; Li, Ruiqin; Zhou, Dantong; Qin, Xinmao; Yan, Wanjun
Abstract: Designing a compound heterojunction photocatalyst is a pragmatic approach for achieving effectively carriers separation and improving light-induced hydrogen production via water splitting. Nonadiabatic molecular dynamics (NAMD) and density functional theory (DFT) methods were used to thoroughly analyze the photo-induced carrier transfer and photocatalytic capabilities of TiO2 /ZnS heterojunction. The calculations indicate that the heterojunction composed of TiO2 (101) slab and ZnS (110) slab featured suitable band gap and enhanced visible light absorption. According to the NAMD calculations, it is possible to classify the TiO2 /ZnS heterojunction as an S-scheme photocatalyst with a potent redox capability. In TiO2 /ZnS heterojunction, the inherent electric field and band bending cause carriers with weak (strong) redox abilities to recombine (separate) at the interface. Particularly, both the Ti and S active sites in the TiO2 /ZnS heterojunction could spontaneously photo-catalyze hydrogen generation under different pH conditions. The theoretical solar-to-hydrogen conversion efficiency of the heterojunction can reach 23.46%. Consequently, our research not only identified an S–scheme photocatalyst for hydrogen production, but provided an approach for developing high-performance hydrogen evolution reaction photocatalysts. Highlights: The TiO2 /ZnS heterojunction can be classified as an S–scheme photocatalyst with a strong redox ability. The formation of a built-in electric field promotes the effective separation of electron–hole pairs. The theoretical STH efficiency of the heterojunction can reach 23.46%.